Book Review: Produção do espaço. Emancipação social, o comum e a “verdadeira democracia” [Space production. Social emancipation, the common and the “true democracy”], by Alvaro Ferreira, João Rua e Regina Célia de Mattos (Org.) - Zanotelli, Claudio (Geografares, 2019)
Book Review: Produção do espaço. Emancipação social, o comum e a “verdadeira democracia” [Space production. Social emancipation, the common and the “true democracy”], by Alvaro Ferreira, João Rua e Regina Célia de Mattos (Org.) This book is the result of the IV Simpósio Internacional Metropolização do Espaço, Gestão Territorial e Relações Urbano-Rurais [International Symposium Metropolization of Space, Territorial Management and Urban-Rural Relations] organized by PUC-Rio in 2018. The book indicates in the Introduction that we are “In the midst of darkness, looking for (im)possible paths” and, in its first paragraph, tells us that “Utopia does not combine with pessimism. We are utopians, not pessimists. Our horizon is the construction of a true democracy, social emancipation, the common use of space with greater social justice. Thus, we continue to believe in a possible impossible, even if the current moment, regardless how reactionary it appears, does not invite us to think in that direction (or, on the contrary, for this very reason, it invites; or rather, imposes itself)”. The book was made with 18 different contributions that navigate between criticism and the indication of new paths and new spaces of thinking and acting for spatial justice and the common.